Conceptual Design of Smart Phone-based Public Reporting System for Unordinary Events Occuring in Streams - Wan Faizal, Wan Ishak (2014)
The rapid advancement of smartphone-based technologies in South Korea has introduced new opportunities to administrators responsible for stream water quality monitoring programs. The sensing functionalities of a smartphone can be used as a handheld monitoring and reporting system using the people-centric sensing approach. Unordinary events occuring in stream can be captured and reported by the public using their handheld devices. The instant contextual feedback capability of the smartphone-based system in the form of geolocation, time, user's description and image data will be very useful to the public, authorities and the research communities in the area of water quality management. This paper proposes a conceptual design of smartphone-based public reporting system to inform in ad-hoc of unordinary event occurring in a stream.